Hubungan Antara Resiliensi Dengan Stres Pada Mahasiswa Fakultas Psikologi Universitas Muhammadiyah Surakarta - Putri Widyawati, Rosalia, Dra. Zahrotul Uyun, M. Si, Psi (2017)
Students experience a transition from late adolescence to early adulthood which is a difficult and critical stage of development that can lead to stress. The task of development during this period requires a major change in attitude and behavior so as to be able to direct themselves and be able to take decisions to achieve the expected goals. Various conditions and challenging situations that cause students need resilience to be able to adjust themselves and still be able to develop themselves well in accordance with the competencies held by students with full responsibility, more critical and more courageous in stating the facts and reality that exists. This study aims to determine the relationship between resilience with stress on the students of Psychology Faculty of Muhammadiyah University of Surakarta. Hypothesis in this study that there is a negative relationship between resilience with stress on students Psychology Faculty of Muhammadiyah University of Surakarta. The population in this study are all students who are still actively attending lectures at the Faculty of Psychology University of Muhammadiyah Surakarta from the force of 2012 until the force of 2016 without distinguishing the gender.The sample in this study amounted to 100 subjects taken with quota sampling technique. The measuring instrument used is resilience scale with reliability 0,911 and stress scale with reliability 0,787. The results of this study indicate that there is a negative relationship between resilience with stress on students of Psychology Faculty of Muhammadiyah University of Surakarta. The relationship is shown from product moment correlation result obtained r = -0,583 and p = 0,000 (p <0,01). The magnitude of the contribution of resilience to stress by 34%. This means there are still some other variables that affect stress on the students of the Faculty of Psychology University of Muhammadiyah Surakarta by 66%. In addition, based on the results of the stress category on the subjects classified as moderate and categorization of resilience in subjects classified as low. The results of this study imply the importance of resilience to stress in students. Keywords : Resilience, Stress, Student